PKU bagi MIM Paremono melalui Media Boneka Horta dalam Pembelajaran Tematik Kurikulum 2013 - Norma Dewi Shalikhah; Ayu Faiza Algifahmy (Publikasi Pendidikan, 2019)
The service program was held at MIM Paremono based on several identification problems such as teachers not using learning media in learning processes, lack of understanding about making learning media effective and efficient, and not caring characters environment in students. This service activity has several objectives, namely 1) Increasing the creativity of teachers and students in developing learning media, 2) Applying to students the character of environmental care. The specific target to be achieved through this service is 1) Train the creativity of teachers and students, 2) Cultivate the character of caring for the environment, and 3) Students can treat plants through the media of horta dolls. To achieve these objectives, carried out using the action research method. Stages of activities begin with preparations including permit activities, preparing technology and arranging schedules; implementation includes socialization, practice, and assistance; and preparation of reports. The results of this service are the character of environmental care in students began to appear, and produce effective learning media in the form of horta dolls in thematic learning the theme of caring for sub-theme animals and plants caring for plants.Keywords: horta doll media, care for the environment